Autumn of Modernism. - Benedetti, Lorenzo; De Vleeshal, Middelburg (Amsterdam Roma Publications, : 2012.)
Boelens, Gwenneth ; Dieleman, Piet ; gerlach en koop ; van der Heide, Sara ; Hendriks, Martijn ; van der Hurk, Bas ; Johannesma, Rob ; Mater, Katja ; Nagtzaam, Marc ; Pisano, Falke ; Stavast, Petra ; Suter, Batia ; Torenbosch, Remco ; in 't Veld, Martijn
Autumn of Modernism, De Vleeshal, Middelburg, from 15 January till 24 March 2012
kunstcatalogus